Comparative pharmacokinetics of yohimbine in steers, horses and dogs. - Jernigan, A D (1988)
In steers, horses and dogs, the comparative pharmacokinetics of yohimbine were determined using model-independent analysis. The intravenous dose of yohimbine was 0.25 mg/kg of body weight in steers, 0.075 or 0.15 mg/kg in horses, and 0.4 mg/kg in dogs. The mean residence time (+/- SD) of yohimbine was 86.7 +/- 46.2 min in steers, 106.2 +/- 72.1 to 118.7 +/- 35.0 min in horses, and 163.6 +/- 49.7 min in dogs. The mean apparent volume of distribution of yohimbine at steady state was 4.9 +/- 1.4 L/kg for steers, 2.7 +/- 1.0 to 4.6 +/- 1.9 L/kg for horses, and 4.5 +/- 1.8 L/kg for dogs. The total body clearance of yohimbine was 69.6 +/- 35.1 mL/min/kg for steers, 34.0 +/- 19.4 to 39.6 +/- 16.6 mL/min/kg for horses, and 29.6 +/- 14.7 mL/min/kg for dogs. Between-species comparisons indicated that the mean area under the serum concentration versus time curve was significantly greater (P less than 0.05) in dogs than in horses. There were no significant differences (P greater than 0.05) between the means for the apparent volume of distribution, clearance, mean residence time, terminal rate constant, and area under the curve between horses given the two doses of yohimbine. The harmonic mean effective half-life (+/- pseudo standard deviation) of yohimbine was 46.7 +/- 24.4 min in steers, 52.8 +/- 27.8 to 76.1 +/- 23.1 min in horses, and 104.1 +/- 32.1 min in dogs. The data may explain why steers, horses, and dogs given certain sedatives and anesthetics do not relapse when aroused by an intravenous injection of yohimbine hydrochloride.